ANALISIS ISI CERAMAH BUYA YAHYA â€œKETIKA UJIAN HIDUP TERASA MELELAHKANâ€ PADA CHANNEL YOUTUBE AL-BAHJAH TV - Maghfiroh, Lailatul; Masruroh, Sayidah Afyatul (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2023)
Buya Yahya in a short time has received a lot of attention from the public in an effort to spread Islamic da'wah on YouTube social media through the Al-Bahjah TV channel. This is due to the way Buya Yahya speaks in his lectures which always sound and look interesting, the use of language that is easy to understand, his lectures which are not only consumed by the Indonesian public but also abroad. This research focuses on, the message of Buya Yahya's lecture "When Life's Exams Feel Tired" on the Al-Bahjah TV YouTube channel. The results of this study indicate that the message of Buya Yahya's lecture contained in the YouTube channel Al-Bahjah TV with the title "Ketika Ujian Hidup Terasa Melelahkan" is a message of aqidah including human faith in Allah. Moral messages include the behavior and character of a person in everyday life such as patience, forgiveness, open mindedness, always living in peace and not envying each other, being arrogant, fighting against each other, inciting one another. And the message of Shari'ah includes matters of worship and law. The researcher argues that the da'wah message is very relevant to the current conditions of development, because it is a message of vigilance regarding information that is circulating, because not all of it comes from the right sources.